The Effect of Entrepreneurial Financing Choice Mediation: Financial Literacy on Sustainability of SMEs - Rani Sintya; Erni Masdupi (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Small and Medium Enterprises have great potential but face difficulties in achieving sustainability due to limited financial literacy and entrepreneurial financing choices.Purpose: This research aims to investigate the influence of financial literacy on the sustainability of SMEs in West Sumatra and explore the mediating effect of entrepreneurial financing choice.Design/methodology/approach: This type of research is quantitative research using a survey approach. This research involved 247 SMEs and data collection was carried out through questionnaires. This hypothesis testing was carried out by structural equation modeling (SEM) using SmartPLS 4.1.3Finding/Results: These findings indicate that financial literacy significantly positively increases the sustainability of SMEs. However, financial literacy on entrepreneurial financing choices has a significant negative impact, as well as entrepreneurial financing choices on sustainability has a significant negative impact. Apart from that, the mediating effect of entrepreneurial financing choice in influencing financial literacy on sustainability has a significant positive impact. Conclusion: This research shows that financial literacy positively influences sustainability in SMEs. Although entrepreneurial financing choice has a negative relationship with financial literacy and sustainability. However, the mediation role has a positive relationship. Originality/value (state of art): Entrepreneurial financing choice is a choice made by SMEs in seeking and obtaining funding sources, both internal and external, but SMEs have obstacles in accessing external funding. Keywords: entrepreneurial financing choice, financial literacy, SMEs, sustainability